Total Synthesis of Patulone: A Natural Xanthonoid Possessing a Geminally Diisoprenylated Structure - Kobayashi, Ryouma; Watabe, Yu; Fujimoto, Yuuki; Yanai, Hikaru; Matsumoto, Takashi (Synlett, 2022)
The first total synthesis of patulone, a plant metabolite possessing a unique 1,1-diisoprenyl-1H-xanthene-2,9-dione structure, is described. Starting from a 1-fluroxanthone derivative with suitable substitution pattern, the pivotal gem-diisoprenylation was efficiently accomplished by implementing twice the sequence of addition of isoprenyl Grignard reagent to the carbonyl at C9 and anion-accelerated oxy-Cope rearrangement.
Keywords: total synthesis; xanthone; geminal substitution; isoprenylation; oxy-Cope rearrangement; regioselectivity